Pengaruh Profitabilitas, Likuiditas, Kualitas Audit, Corporate Governance dan Ukuran Perusahaan terhadap Penghindaran Pajak - I Nyoman Agus Wahyu Anggara; Yenny Verawati; Desak Ayu Sriary Bhegawati (Jurnal Inovasi Akuntansi)
This study aims to analyze the effect of profitability, liquidity, audit quality, corporate governance and company size on tax evasion. The sample used is 193 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. Determination of the sample using purposive sampling technique. The data analysis technique used is multiple linear regression analysis.The results of this study indicate that the variable profitability, audit committee and firm size have a positive effect on tax evasion. While the audit quality variable has a negative effect on tax evasion. And the variable liquidity and independent commissioners have no effect on tax evasion. For further research, this research can be developed using other variables that have an influence on tax evasion.